PENERAPAN MODEL PEMBELAJARAN MEGABRAIN UNTUK MENINGKATKAN HASIL BELAJAR KOSMETIKA TRADISIONAL KELAS X DI SMK NEGERI 3 BOGOR - Dwagusta Renolanda, Fita (Jurnal Tata Rias, 2014)
Abstract This study is a Class Action Research (classroom action research) with a class action for 3 cycles . Each - each cycle consisting of the above four stages , namely : ( 1 ) planning , ( 2 ) Implementation , ( 3 ) Observation and ( 4 ) Reflection . This study aims to improve student learning outcomes in subjects traditional cosmetics using megabrain learning model . The data collection was done by using tests , observations and interviews . Data were analyzed using qualitative and quantitative techniques , which uses qualitative to measure the response and attitude of students , while quantitative ie to measure learning outcomes .Place the implementation of this class action carried out in the tenth grade skin care at SMK 3 Bogor with the number of students 28 students . Allocation of time each - each cycle of 2 x 45 minutes on November 24 - December 16, 2014.The results of this study showed that using learning model megabrain on the subjects of traditional cosmetics can improve the results of class X student skin beauty SMK 3 Bogor . Obtaining the average - average grade increased from pretest and posttest pretest cycle 3. In the implementation of obtaining the average - average class subjects traditional cosmetics by 56.6 later in the cycle I average results - average increased to 71.6 with the highest score of 80 and the lowest value of 60 .it has not reached a predetermined value on the target absorption , therefore implemented the learning cycle II . Learning the second cycle average - average class traditional eye cosmetic elajaran obtained increased compared to the first cycle of 79.8 with the highest value and lowest 85 70. From the results of the second cycle study , it was decided to continue the implementation of the third cycle was obtained average - average class subjects traditional cosmetics increase compared to the second cycle is equal to 86.6 with the highest value and lowest value 95 75. the results of this study also has implications for the application of learning models megabrain on the subjects of traditional cosmetics and can be connected with a case study . Keywords: Megabrain, Learning Outcomes, Traditional Cosmetics Abstrak Penelitian ini merupakan Penelitian Tindakan Kelas (Classroom Action Research) dengan melakukan tindakan kelas sebanyak 3 siklus. Masing – masing siklus terdiri dari atas 4 tahapan yaitu : (1) Perencanaan, (2) Pelaksanaan, (3) Pengamatan dan (4) Refleksi. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa pada mata pelajaran kosmetika tradisional dengan menggunakan model pembelajaran megabrain.Pengumpulan data dilakukan dengan teknik tes, pengamatan dan wawancara.Teknik analisis data menggunakan teknik kualitatif dan kuantitatif, dimana kegunaan kualitatif untuk mengukur respon dan sikap siswa sedangkan kuantitatif yaitu untuk mengukur hasil belajar. Tempat pelaksanaan tindakan kelas ini dilaksanakan dalam kelas X kecantikan kulit di SMKN 3 Bogor dengan jumlah siswa 28 siswa. Alokasi waktu masing – masing siklus sebesar 2 x 45 menit pada tanggal 24 November – 16 Desember 2014. Hasil penelitian ini, menunjukan bahwa menggunakan model pembelajaran megabrain pada mata pelajaran kosmetika tradisional dapat meningkatkan hasil belajar siswa kelas X kecantikan kulit SMKN 3 Bogor.Perolehan rata - rata kelas meningkat dari pretest dan posttest siklus 3. Pada pelaksanaan pretest memperoleh rata – rata kelas mata pelajaran kosmetika tradisional sebesar 56,6 kemudian dalam siklus I hasil rata – rata meningkat menjadi 71,6 dengan nilai tertinggi 80 dan nilai terendah 60. Hal tersebut belum mencapai nilai yang telah ditetapkan pada target daya serap, oleh karena itu dilaksanakan pembelajaran siklus II. Pembelajaran siklus II rata – rata kelas mata elajaran kosmetika tradisional yang diperoleh meningkat dibandingkan siklus I sebesar 79,8 dengan nilai tertinggi 85 dan terendah 70. Dari hasil belajar siklus II, diputuskan untuk melanjutkan pelaksanaan siklus III diperoleh rata – rata kelas mata pelajaran kosmetika tradisional meningkat dibandingkan siklus II yaitu sebesar 86,6 dengan nilai tertinggi 95 dan nilai terendah 75. Hasil penelitian ini juga berimplikasi pada penerapan model pembelajaran megabrain pada mata pelajaran kosmetika tradisional dan bisa dihubungkan dengan studi kasus. Kata Kunci: Megabrain, Hasil Belajar, Kosmetika Tradisional.